Boosting the Catalytic Performance of Metal–Organic Frameworks for Steroid Transformations by Confinement within a Mesoporous Scaffold. (25th September 2017) - Cirujano, Francisco G.; Luz, Ignacio; Soukri, Mustapha; Van Goethem, Cedric; Vankelecom, Ivo F. J.; Lail, Marty; De Vos, Dirk E.
Abstract: Solid‐state crystallization achieves selective confinement of metal–organic framework (MOF) nanocrystals within mesoporous materials, thereby rendering active sites more accessible compared to the bulk‐MOF and enhancing the chemical and mechanical stability of MOF nanocrystals. (Zr)UiO‐66(NH2 )/SiO2 hybrid materials were tested as efficient and reusable heterogeneous catalysts for the synthesis of steroid derivatives, outperforming the bulk (Zr)UiO‐66(NH2 ) MOF. A clear correlation between the catalytic activity of the dispersed Zr sites present in the confined MOF, and the loading of the mesoporous SiO2, is demonstrated for steroid transformations.